2018
DOI: 10.1108/cms-10-2017-0294
|View full text |Cite
|
Sign up to set email alerts
|

Linking authoritarian leadership to employee creativity

Abstract: Purpose The present study aims to examine how and when authoritarian leadership affects employee creativity. Based on social exchange theory and team identification literature, the present research attempts to simultaneously explore how leader–member exchange (LMX) and team identification serve as two important mediating processes in the relationship between authoritarian leadership and employee creativity. Furthermore, this research uncovers the mechanism under which conditions the effects of authoritarian le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 68 publications
4
62
1
Order By: Relevance
“…A number of previous studies on organic organisations display that a low power distance creates a low interaction gap between superiors and subordinates in a low hierarchical organisation structure (Daniels & Greguras, 2014;Gu et al, 2018). In this power distance orientation, superiors show a number of tendencies, such as allowing active participation, obtaining feedback from subordinates on matters of importance and sharing up-to-date information (Hofstede & Hofstede, 2005;Gu et al, 2018).…”
Section: The Relationship Between Organisational Justice Power Distamentioning
confidence: 99%
See 4 more Smart Citations
“…A number of previous studies on organic organisations display that a low power distance creates a low interaction gap between superiors and subordinates in a low hierarchical organisation structure (Daniels & Greguras, 2014;Gu et al, 2018). In this power distance orientation, superiors show a number of tendencies, such as allowing active participation, obtaining feedback from subordinates on matters of importance and sharing up-to-date information (Hofstede & Hofstede, 2005;Gu et al, 2018).…”
Section: The Relationship Between Organisational Justice Power Distamentioning
confidence: 99%
“…They are practised at varying degrees in different organisational settings within the same and/or different countries (Daniels & Greguras, 2014;Muhammad et al, 2020). The findings from previous studies have shown that the role of power distance as a moderating variable has investigated leadership styles and individual attitudes and behaviour (e.g., performance, team effectiveness and creativity) within collectivism and individualism cultures (Gu et al, 2018;Purwanto, 2018). According to Purwanto (2018), most organisational culture studies have spotted the level of power distance as an important moderating variable between particular features of organisational justice (e.g., quality of relationship between leaders and subordinates, participative decision making and empowerment) and job satisfaction (Fock et al, 2013;Hauff & Richter, 2015;Rafiei & Pourreza, 2013).…”
Section: The Relationship Between Organisational Justice Power Distamentioning
confidence: 99%
See 3 more Smart Citations